UMPSA launches Recruitment Drive with Successful Walk-In Interview Session - Wan Jumani, Fauzi; Athirah, Ruzaini (UMPSA, 2025)
KUALA LUMPUR, 3 May 2025 – In a proactive move to strengthen its academic team, Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), held its first-ever walk-in interview session for English language lecturer positions.